Rapid maxillary expansion in the treatment of the functional posterior crossbite: joint noise and electromyographic activity analysis - Diego Jesus Brandariz PIMENTEL; Laís Valencise MAGRI; Melissa de Oliveira MELCHIOR; Guido Artemio MARAÑÓN-VÁSQUEZ; Mirian Aiko Nakane MATSUMOTO; Marcelo Oliveira MAZZETTO (Universidade Estadual Paulista, 2019)
Abstract Introduction The rapid maxillary expansion (RME) reduces the risk of developing structural and functional disorders in the stomatognathic system. Objective To examine the effects of the RME as a treatment for the posterior crossbite, related with the electromyographic activity of the masticatory muscles and the TMJ noises in a population of children. Material and method 13 girls and 7 boys, regardless of the type of malocclusion, with a mean age of 9 years old (± 3), were treated with RME. The electrovibratography analyzed the TMJ noise, and the electromyography analyzed the masticatory muscles before treatment (T0) and after three months of a short-term follow-up (T1). The comparisons of the affected and unaffected sides by the crossbite were performed using Mann-Whitney's test, and to compare data before and after treatment the Wilcoxon's test was used (level of significance: 5%). Result No significant differences were found in the parameters of joint noise in comparison to the sides affected and unaffected by the crossbite, in both T0 and T1 (p>0.05); only the side without the crossbite observed decrease in the peak amplitude of the joint noises after treatment. In the static electromyographic analysis, inter-side differences were observed before and after treatment, since the deliberate unilateral chewing showed greater asymmetry activity in T0 for both sides, which has been corrected after treatment, improving the functional chewing. Conclusion The proposed treatment did not lead to the occurrence of joint noises and improved the functional pattern of electromyographic activity during chewing at the end of treatment.